Vibroakustische Analyse eines elektrischen Radnabenmotors und Optimierung durch geeignete Steuerungsansätze - Stretz, Dominik (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2023)
This work deals with the mechanisms of disturbing noises at the electric wheel hub motor and describes a multiphysical model which simulates them. From this, countermeasures are derived and evaluated. A vibroacoustical optimized control approach, was developed and applied to the system. Furthermore, limitations and the interaction of the optimized control approach with the motor control are examined more detail.